In Coronary Angiography, Transradial Versus Transfemoral Access: What Are Patients’ Perspectives? - Kumral, Zeynep; Yıldırım, Halil İbrahim and Kurşun, Yağmur and Kodal, Fatmanur and Kış, Mehmet (Journal of Cardiology and Cardiovascular Medicine, 2024)
Objective: Current guidelines favour radial access (TRA) over femoral access (TFA) for percutaneous coronary interventions due to lower bleeding risks and quicker patient recovery. This study compares patient satisfaction and complications between the two methods to identify the most suitable access route in coronary angiography (CAG). Materials and methods: A total of 152 patients who underwent CAG between February and June 2024 at our clinic were included. The operator and patient made access site decisions. Patients were surveyed 24 hours post-procedure, and complications were tracked for one month. The primary endpoint was patient satisfaction, while complications were classified as minor and major bleeding, pseudoaneurysm, hematoma, and spasm. Results: Of the 152 patients, 33% (n = 50) underwent TRA and 67% (n = 102) underwent TFA. Minor bleeding occurred in 16% (n = 24) and major bleeding in 0.02% (n = 3) patients. Pre-procedure anxiety, satisfaction with the access method, and awareness of TRA showed no significant differences between groups. However, post-procedure pain was higher in the TRA group (46% vs. 15%, p < 0.001), and systolic blood pressure was slightly elevated in the TRA group. Anxiety was more common in females, while elderly and obese patients showed no significant differences in bleeding or complications. Conclusion: Despite TRA’s benefits, no significant difference in satisfaction between TRA and TFA was observed. Patient preferences, radial artery spasms in females, and improved TFA techniques may influence outcomes. A shared decision-making process between operator and patient seems optimal for access site choice, with further investigation into patient satisfaction factors warranted.